Plant mediated synthesis of flower-like Cu2O microbeads from Artimisia campestris L. extract for the catalyzed synthesis of 1,4-disubstituted 1,2,3-triazole derivatives - Abdelbaki, Halla; Djemoui, Amar; Souli, Lahcene; Souadia, Ahmed; Ouahrani, Mohammed Ridha; Djemoui, Brahim; Lahrech, Mokhtar Boualem; Messaoudi, Mohammed; Ben Amor, Ilham; Benarfa, Adel; Alsalme, Ali; Bechelany, Mikhael; et al. (Frontiers in Chemistry, 2024)
This study presents a novel method for synthesizing 1,4-disubstituted 1,2,3-triazole derivatives through a one-pot, multi-component addition reaction using flower-like Cu2O microbeads as a catalyst. The flower-like Cu2O microbeads were synthesized using an aqueous extract of Artimisia Campestris L. This extract demonstrated the capability to reduce and stabilize Cu2O particles during their initial formation, resulting in the formation of a porous flower-like morphology. These Cu2O microbeads exhibit distinctive features, including a cubic close-packed (ccp) crystal structure with an average crystallite size of 22.8 nm, bandgap energy of 2.7 eV and a particle size of 6 µm. Their catalytic activity in synthesizing 1,4-disubstituted 1,2,3-triazole derivatives was investigated through systematic exploration of key parameters such as catalyst quantity (1, 5, 10, 15, 20, and 30 mg/mL), solvent type (dimethylformamide/H2O, ethanol/H2O, dichloromethane/H2O, chloroform, acetone, and dimethyl sulfoxide), and catalyst reusability (four cycles). The Cu2O microbeads significantly increased the product yield from 20% to 85.3%. The green synthesis and outstanding catalytic attributes make these flower-like Cu2O microbeads promising, efficient, and recyclable catalysts for sustainable and effective chemical transformations.